2014
DOI: 10.1371/journal.pone.0086295
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA H19 Promotes Glioma Cell Invasion by Deriving miR-675

Abstract: H19 RNA has been characterized as an oncogenic long non-coding RNA (lncRNA) in breast and colon cancer. However, the role and function of lncRNA H19 in glioma development remain unclear. In this study, we identified that H19/miR-675 signaling was critical for glioma progression. By analyzing glioma gene expression data sets, we found increased H19 in high grade gliomas. H19 depletion via siRNA inhibited invasion in glioma cells. Further, we found H19 positively correlated with its derivate miR-675 expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
233
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(247 citation statements)
references
References 29 publications
8
233
1
2
Order By: Relevance
“…Finally, H19 is one of most up-regulated lncRNAs in our RNAseq data, and it has been found to be overexpressed in glioma, where it promotes cell invasion (36). Here, we have shown that I-BET151 and BRD4 knockdown strongly reduce the expression of H19, confirming that functional noncoding RNAs should be taken into consideration when investigating the consequences of drug treatment on the gene expression profile of tumors.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Finally, H19 is one of most up-regulated lncRNAs in our RNAseq data, and it has been found to be overexpressed in glioma, where it promotes cell invasion (36). Here, we have shown that I-BET151 and BRD4 knockdown strongly reduce the expression of H19, confirming that functional noncoding RNAs should be taken into consideration when investigating the consequences of drug treatment on the gene expression profile of tumors.…”
Section: Discussionsupporting
confidence: 63%
“…S1A). Importantly, our analysis identified the previously characterized glioma-enriched lncRNA H19 (36), suggesting that our SMS pipeline robustly identifies lncRNAs overexpressed in glioma. Fig.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Анализ in vitro и in vivo моделей, при которых экспрессия miR-675-5p блокирована, демонстрирует, что при условии низкого содержания кислорода активность и синтез HIF1a в этом случае снижены, ответ на гипоксию, в том числе ангиогенез, не происходит [81]. MiR-675 модулирует экспрессию кадгерина 13 за счёт прямого связывания с его 3¢-UTR [82].…”
Section: (рис 2)unclassified
“…Введение miR-326 может являться новой стратегией терапии [35]. miR-326 ингибируется PI3-киназным каскадом [21] [ [20][21][22], [35], [37] miR-675-5p, ген которой находится внутри гена длинной некодирующей РНК Н19, играет роль в развитии ответа на гипоксию и гипоксия-опосредованном ангиогенезе [81] [81], [82] короткая длина зрелых микро-РНК ограничивает дизайн проб [101]. Несомненным преимуществом RNA-seq является возможность глубокого анализа дифференциальной экспрессии, в том числе поиска вариаций (SNP и др.…”
Section: (рис 2)unclassified